2012
DOI: 10.5534/wjmh.2012.30.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Lower Urinary Tract Symptoms/Benign Prostatic Hyperplasia and Metabolic Syndrome in Korean Men

Abstract: PurposeTo investigate any associations between lower urinary tract symptoms (LUTS)/benign prostate hyperplasia (BPH) and metabolic syndrome (MetS).Materials and MethodsIn all, 1,224 male police officers in their 50s who had participated in health examinations were included. LUTS/BPH was assessed by serum prostate-specific antigen, International Prostate Symptom Score (IPSS), transrectal ultrasonography, maximum urinary flow rate (Q max), and postvoid residual urine volume (PVR). In addition, testosterone was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 13 publications
3
32
0
Order By: Relevance
“…Another study in China [20] indicated that prostate volume was not related to MeS in BPH patients under 50 years of age . In a study of Korean men in their 50 years, no significant differences were found in mean total prostate volume between MetS and without MetS [38]. These inconsistent findings might be explained by the different age distribution.…”
Section: Discussionmentioning
confidence: 77%
“…Another study in China [20] indicated that prostate volume was not related to MeS in BPH patients under 50 years of age . In a study of Korean men in their 50 years, no significant differences were found in mean total prostate volume between MetS and without MetS [38]. These inconsistent findings might be explained by the different age distribution.…”
Section: Discussionmentioning
confidence: 77%
“…In their study, annual transitional prostate volume (TPV) growth rate was significantly higher in BPH patients with MetS as compared with those without MetS (1.019 ml/yr vs 0.699 ml/yr, respectively). After this preliminary work, several authors have documented a possible association between MetS and BPH [14–16] but other authors didn’t confirm this association [17]. Interestingly in a meta-analysis of the available evidence we found that subjects with MetS had significantly higher total prostate volume when compared to those without MetS (+1.8 [95% CI: 0.74;2.87] ml; p  < 0.001) and these datas are in agreement to the present one.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported a positive correlation between MetS and nocturia . However, recent studies on middle‐aged men from health check‐ups did not find that MetS was associated with nocturia …”
Section: Discussionmentioning
confidence: 97%